If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 20 = 0 Reorder the terms: 20 + 7x = 0 Solving 20 + 7x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + -20 + 7x = 0 + -20 Combine like terms: 20 + -20 = 0 0 + 7x = 0 + -20 7x = 0 + -20 Combine like terms: 0 + -20 = -20 7x = -20 Divide each side by '7'. x = -2.857142857 Simplifying x = -2.857142857
| 2x^2-17x+15=0 | | 5y+3=9y-1 | | 7+x=.5(4*2) | | 5x-1=3x+13 | | 5-4k=-(4k+1) | | 6x-12+3x+26=180 | | z^2(x+1)-3z(x+1)-70(x+1)=0 | | (1.1+k)5-7.6=1.6 | | d-4=-13 | | -2(w-7)+lOw=34 | | 7x+2y=7 | | 17+3(z+2)-11z=-7(z+2)+14 | | 20x+53= | | 2p-(1+8p)=4p-21 | | (15-y)+2=2y | | -2x+3=4x+75 | | Y+7-3=12 | | xz^2+z^2-3zx+4z-70x+70=0 | | 200-80=2l+80-80 | | 8r+7=49 | | s=p(1+rt) | | 14+s=-32 | | 4-3n=2n-36 | | -58+58=29p-14p | | 1x+5=3x-1 | | 4(x+5)=6x+4-2x+16 | | 9*0-7=-7 | | 7(m+7)=36-6m | | (x-2)(3+y)=(x-2)(3+y) | | 7m^6+m-3(m^6+4m)= | | .67a-14=61 | | 10x-20= |